Hubungan Pengetahuan, Motivasi Dan Dukungan Keluarga Ibu Hamil Dengan Kepatuhan Pemeriksaan Triple Eliminasi Di Puskesmas Mekarjaya Pandeglang - Nurlaila Nurlaila; Agustina Sari (THE JOURNAL OF Mother and Child Health Concerns, 2021)
Backgrounds: Indonesia's Health Profile in 2018, still 69.95% of pregnancies were tested for HIV and Hepatitis B and the examination found 0.28% of pregnant women who were HIV positive. The number of pregnant women who underwent antenatal care in Banten reached 95.88%, but pregnant women who were tested for HIV found 6,439 (0.27%) pregnant women who were HIV positive. Purpose: The purpose of this study was to determine the relationship between knowledge, motivation and family support of pregnant women with triple elimination examinations at the Mekarjaya Public Health Center in 2022. Methods: This research method uses cross sectional. The population in this study were all pregnant women, the sampling technique in this study used purposive sampling using the Slovin formula with a sample of 67 pregnant women. The analysis in this study used univariate and bivariate analysis using the Chi Square statistical test. Results: The results of this study indicate that there is a significant relationship between knowledge and compliance with the triple elimination examination, obtained P Value of 0.003 and OR 9.500 (2,621-52.219), there is a relationship between motivation and compliance with triple elimination examination, obtained P Value of 0.013 and OR 6.457 (2.621-52.219 ), and there is a relationship between family support and compliance with triple elimination examination obtained P Value 0.003 and OR 9.500 (2.621-52.219). Suggestions from this researcher are that pregnant women can increase motivation and self-confidence and seek as much information as possible about the importance of triple elimination examination.    Pendahuluan: Profil Kesehatan Indonesia tahun 2018, masih 69,95% kehamilan yang dilakukan pemeriksaan HIV dan Hepatitis B dan pemeriksaan tersebut didapatkan 0,28% ibu hamil yang positif HIV. Jumlah ibu hamil yang melakukan pemeriksaan kehamilan di Banten mencapai 95,88%, tetapi ibu hamil yang diperiksa HIV didapatkan 6.439 (0,27%) ibu hamil yang posotif HIV. Tujuan: Untuk mengetahui hubungan pengetahuan motivasi dan dukungan keluarga ibuhamil dengan pemeriksaan triple eliminasi di puskesmas mekarjaya tahun 2022. Metode: Metode penelitian ini menggunakan cross sectional. Populasi dalam penelitian ini semua ibu hamil, teknik sampling dalam penelitian ini menggunakan purposive sampling dengan menggunakan rumus Slovin dengan jumlah sampel 67 ibu hamil.  Analisis dalam penelitian ini menggunakan analisis univariat dan bivariat menggunakan uji statistic Chi Square. Hasil: Penelitian ini meunujukkan bahwa ada hubungan yang signigfikan antara pengetahuan dengan kepatuhan pemeriksaan triple eliminasi diperoleh nilai P Value 0.003 dan OR 9.500 (2,621-52,219), ada hubungan antara motivasi dengan kepatuhan pemeriksaan triple eliminasi diperoleh  P Value 0.013 dan OR 6.457 (2.621-52,219), dan ada hubungan antara dukungan keluarga dengan Kepatuhan pemeriksaan triple eliminasi diperoleh P Value 0.003 dan OR 9.500 (2.621-52,219). Saran dari peneliti ini adalah agar ibu hamil dapat meningkatkan motivasi dan kepercayaan diri serta mencari informasi sebanyak-banyaknya mengenai pentingnya pemeriksaan triple eliminasi.